The Influence of Live Streaming and Content Quality on Purchase Interest in Credifox Products on TikTok Shop - Enggar Widianingrum; Rani Suryani; Mahisa Gibran Putra Hermanto (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of live streaming and content quality on purchase intention for Credifox products on TikTok Shop, both partially and simultaneously. The research employs a quantitative method with a non-probability sampling technique, involving 100 respondents. Data analysis was conducted using statistical quantitative methods and multiple linear regression with the aid of SPSS 25 software. The findings indicate that, partially, live streaming significantly influences purchase intention, with a t-value of 4.571 > t-table 1.985 and a significance level of 0.000 < 0.05. Similarly, content quality also has a significant influence on purchase intention, as shown by a t-value of 3.152 > t-table 1.985 and a significance level of 0.002 < 0.05. Simultaneously, live streaming and content quality have a positive and significant influence on purchase intention for Credifox products on TikTok Shop, with an F-value of 74.834 > F-table 3.100 and a significance level of 0.000 < 0.05.